Applicability of infrared thermography in dentistry: An integrative review (Research, Society and Development, 2021)
This study aimed to carry out an integrative review to analyze the applicability of infrared thermography in Dentistry. For the search, in the Scielo and Pubmed databases, the following keywords were used: “Thermography”; "Body Temperature"; "Microcirculation"; "Dentistry"; “Oral”, using the Boolean operator “AND”. Included in this review were studies that used thermography in the follow-up of therapies, as well as clinical and laboratory studies, excluding studies not related to the objective of this research, studies conducted over a period of more than five years, course completion papers, dissertations, works published in duplicates, annals and letters to the editor. Accordingly, 140 articles were found. After screening by titles and abstracts, a total of 117 were excluded. At the end, 15 studies were included in this review. Based on the research carried out, it appears that there is still no significant number of articles that address the applications of thermography in Dentistry, and there are still several areas that can use it as an effective diagnostic and investigation tool.